Rohis Movement at Two Senior High Schools of Yogyakarta in Actualizing the Hijrah Text of Qur'an Verses in Islamic Education Book: Gerakan Rohis di Dua Sekolah Menengah Atas di Yogyakarta dalam Mengimplementasikan Teks Hijrah Ayat-Ayat Al-Qur'an dalam Buku Pendidikan Islam - Hadi Muhtarom; Ahmad Shofiyuddin Ichsan (Chalim Journal of Teaching and Learning, 2025)
This research aimed to explore the Islamic Spiritual Movement (Rohis) in two State Senior High Schools (SMA) in Yogyakarta, focusing on how they actualize the Qur'anic texts found in Islamic Education (PAI) books and their collections. Employing a qualitative case study approach, the researchers collected data through observation, interviews, and documentation. For data analysis, they applied data reduction, data presentation, and conclusion. The findings reveal that the Rohis administrators' understanding aligns with Hermeneutical Theory, which emphasizes the interpretation of texts within their contexts. Specifically, Rohis administrators actively engage with Qur'anic verses as guiding principles for daily life. They attempt to comprehend both the contemporary context and the historical significance of Islam's glory during the era of the Caliphate. Furthermore, they contextualize these teachings in their personal lives and extend their understanding to influence the public sphere, including their school communities. This approach highlights the dynamic and practical application of religious texts in shaping spiritual and social life.